Ecological Psychology and Enactivism: Perceptually-Guided Action vs. Sensation-Based Enaction1 - Read, Catherine; Szokolszky, Agnes (Frontiers in Psychology, 2020)
Ecological Psychology and Enactivism both challenge representationist cognitive science; the two approaches, however, have to date only begun to engage in dialogue. This dialogue has been set in motion lately. In order clearly to see what these two approaches offer and how they relate to each other, misunderstandings and misreadings must be discarded and further conceptual clarification is required. This paper enters the dialogue by examining the core concepts of both approaches, distinctly relying on the foundational sources, that is, the writings of James J. Gibson and Francesco Varela. The analysis focuses first on the biological roots of Enactionism and Ecological Psychology. Next, it takes up a detailed examination of the ecological critique of sensation based perception theories and the ecological concept of mutualism. The analysis concludes that both approaches take action as central, but their definitions of what action is and how it takes place differ radically. Enactivists concentrate on embodiment and sensation-based enaction, whereas ecological psychologists ground their view in direct perception and ecological action. This paper argues that these are profound differences that must be recognized and acknowledged. This does not mean, however, that there is no point to the dialogue. Both Enactivism and Ecological Psychology are developing enterprises that need to give elaborate answers to questions regarding brain level processes, knowing and feeling, consciousness, and phenomenological experience. The paper concludes that the goal is not to seek convergence, but to continue interaction with to each other, leaving open the possibility of cross-fertilization.